Promoter hypermethylation is associated with tumor location, stage, and subsequent progression in transitional cell carcinoma. - Catto, J; Azzouzi, A; Rehman, I; Feeley, K; Cross, S; Amira, N; Fromont, G; Sibony, M; Cussenot, O; Meuth, M; Hamdy, F (2005)
PURPOSE: Transitional cell carcinoma (TCC) is a pan-urothelial disease characterized by multiplicity. Although little is known about the molecular events in upper-tract TCC, similar carcinogenic mechanisms are thought to occur throughout the urinary tract. However, we have previously shown that distinct patterns of microsatellite instability occur in upper and lower urinary tract TCC, suggesting biologic differences between these tumors. Here we investigate the extent of promoter hypermethylation in TCC throughout the urinary tract. PATIENTS AND METHODS: Tissue was obtained from 280 patients (median follow-up, 56 months) whose tumors comprised 116 bladder and 164 upper-tract tumors (UTT). Analysis for hypermethylation at 11 CpG islands, using methylation-sensitive polymerase chain reaction and bisulfite sequencing, was performed for each sample and compared with the tumor's clinicopathologic details, microsatellite instability status, and subsequent behavior. RESULTS: Promoter methylation was present in 86% of TCC and occurred both more frequently and more extensively in UTT (94%) than in bladder tumors (76%; P < .0001). Methylation was associated with advanced tumor stage (P = .0001) and higher tumor progression (P = .03) and mortality rates (P = .04), when compared with tumors without methylation. Multivariate analysis revealed that methylation at the RASSF1A and DAPK loci, in addition to tumor stage and grade, were associated with disease progression (P < .04). CONCLUSION: Despite morphologic similarities, there are genetic and epigenetic differences between TCC in the upper and lower urinary tracts. Methylation occurs commonly in urinary tract tumors, may affect carcinogenic mechanisms, and is a prognostic marker and a potential therapeutic target.